Progressive Efforts in the Implementation of Integrated Water Resources Management (IWRM) in Uganda. - Turyasingura, Benson; Akatwijuka, Rogers; Tumwesigye, Wycliffe; Ayiga, Natal; Ruhiiga, Tabukeli Musigi; Banerjee, Abhishek; Benzougagh, Brahim; Frolov, Denis (Kabale University, 2024)
Worldwide, water is essential in creating the environment and human life. Uganda’s Vision 2040 promises general use and safe access to drinking water for all Ugandans. Today, 14% of the population in Uganda have access to potable managed water, and 78% of rural communities have access to the sanitation system, and by 2040, the number is expected to have doubled.“ If the population is to exercise its constitutional right to receive a dependable, safe, and inexpensive water supply, it is imperative that infrastructure for water supply be provided. We assessed the progressive efforts in the implementation of integrated water resources management in Uganda, challenges, opportunities, and policies for water management.” Explorations for the keywords “water” AND “water resources”, AND “water management” were used in this study. A total of 125 papers were selected for this study from 2013 to 2022, from Scopus, Google Scholar, Science Direct, and Web of Science, that were found relevant for this study and were selected and discussed. According to findings, the United States, the United Kingdom, China, and India were the leading publications. In the analysis of sources of journals by publications, the Science of The Total Environment was the leading. According to the analysis by the organizations, the leading was Wageningen University and Research, followed by the University of Chinese Academy of Sciences. It was concluded that the problems of effectiveness in water resource management are still a global change and little effort has been made. To bridge the gap from science to policymaking in the water resources nexus, it is vital to enhance stakeholder collaboration, water resource tradeoffs, and regional development and preservation by optimizing the ecological water resource pattern.